Disaster recovery and business continuity: A case of MSMEs in Dar es Salaam - Tumpale Sakijege (Jàmbá)
A large number of micro, small and medium enterprises (MSMEs) in developing countries operate in informal settlements. Most of these settlements exist in hazardous environment despite being affected by floods. This research discusses the scarcity of knowledge on the resilience of businesses operating in Kigogo flood-prone informal settlements in Dar es Salaam. It especially focusses on MSMEs. Although recovery of MSMEs has been intensively studied worldwide, in Tanzania it is downgraded. This article is set to bridge this glaring gap focusing on MSMEs recovery after floods. The research methodology employed quantitative research design by completing questionnaires through interviews. A total of 202 owners of MSMEs were interviewed. While content analysis was used to analyse qualitative data, the research further employed a logistic unit model to analyse factors explaining recovery of MSMEs after floods. The study revealed a statistically significant association between the recovery of MSMEs and suitable plans for safeguarding business, personal savings, profit (saving from business) and government support. Other factors include family and friend’s support, business continuity training, longevity in business operation, pre-disaster mitigation measures, critical destruction to business facilities, and running several businesses. Strength, Weaknesses, Opportunities and Threat (SWOT) analysis of the business environment where MSMEs operate revealed a number of issues that inform policymakers, urban planners and environmentalists on what can be done to enhance recovery and hence promote sustainable development.